KONSTRUKSI MAKNA â€œTAKKO BINOTOâ€ BAGI PELAKU DI DESA MENAMING KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Insani, Fitri; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is motivated by the phenomenon of Takko binoto which has long been a fairly complex problem in which many male and female couples in realizing their desire to carry out a marriage contract by way of binoto takko. Because they felt that there was a conflict from parents about the relationship they had endured, Takko Binoto was chosen as a way out. Takko Binoto happened because it was influenced by economic aspects and low levels of education. The purpose of this research is to find out the motives behind the couple doing Takko Binoto, understanding the meaning of Takoto Binoto and knowing the communication experience for Takko Binoto actors in Menaming village, Rambah District, Rokan Hulu Regency.This study uses qualitative research methods with a phenomenological approach. Data collection techniques consist of in-depth interviews, observation and documentation. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. The data validity checking technique uses triangulation. The gathering of informants in this study used the Snowball Technique with the number of informants as many as 5 pairs of Takoto Binoto actors.The results of this study show the first few motives of takoto binoto actors in the village menaming are divided into two motives because (because motive) and motives of hope (in order to motive). As for the motives because for Takoto binoto actors are economic factors, mutual love, free promiscuity and low education. Then in order to motive Takko Binoto's perpetrators are motives to provide a deterrent effect, happy motives for the world and the hereafter and motives to ease the burden on the family's economy. Second, the meaning of Takko Binoto for actors in the village of Menaming is the meaning of Takoto Binoto as the destiny of God, Takko Binoto as a result of past actions, and Takko Binoto as the last choice to be taken. Third, the Takko Binoto perpetrators' communication experience consists of pleasant (positive) communication experiences and unpleasant communication experiences. a pleasant (positive) communication experience for Takko Binoto's perpetrators, namely getting a life partner to feel extraordinary love from her husband. Then the unpleasant (negative) communication experience for Takko Binoto actors is getting negative comments, being ostracized from the family and the environment, and family conflicts. Keywords: Construction Meaning, Takko Binoto, Motives